A STUDY ON THE ABILITY OF THE FIRST GRADE STUDENTS OF SMAN 1 SIMPANG KANAN ROKAN HILIR IN READING COMPREHENSION - Tri Wulan Dari; Hadriana '; Afrianto ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This descriptive research aimed to find out the ability of the first grade students of SMAN 1 Simpang Kanan Rokan Hilir in Reading Comprehension. The population of the research is the first grade students of SMAN 1 Simpang Kanan and the sample is 32 students. The instrument used in this research is a reading test. This reading test consisted of 35 questions . Based on the data analysis, it can be concluded that the ability of the first grade students of SMAN 1 Simpang Kanan Rokan Hilir in reading comprehension is in good level with mean score is 63.14. Further, the result shows that there are 2 students who are in excellent level, 18 students are in good level, 8 students are in average level, and 4 students are in poor level.Key Words: Students’ Ability, Reading Comprehension